Petroleum Depletion Property and Microbial Community Shift After Bioremediation Using Bacillus halotolerans T-04 and Bacillus cereus 1-1 - Deng, Zhenshan; Jiang, Yingying; Chen, Kaikai; Gao, Fei; Liu, Xiaodong (Frontiers in Microbiology, 2020)
Bioremediation of crude oil contaminated environments is an economical, low-maintenance, environmentally friendly technology and has attracted increasing attention in recent years. In the present study, two efficient crude oil degrading bacteria strains were isolated from soils contaminated with crude oil. Phylogenetic analysis suggested they belonged to genus Bacillus, and were designated as Bacillus cereus T-04 and Bacillus halotolerans 1-1. The crude oil depletion of each strain under different conditions was tested. The optimum conditions for both strains’ oil degradation was pH 7, 15–20 g/L NaCl concentration, and 5–15 g/L original oil concentration. The crude oil depletion rate could reach to 60%–80% after 20 days of treatment. The crude oil bioremediation simulation tests revealed that the bioremediation promoted the depletion of crude oil to a large extent. The inoculum group with inorganic medium showed the highest crude oil depletion (97.5%) while the crude oil depletion of control group was only 26.6% after 180 days of treatment. High-throughput sequencing was used to monitor the changes of microbial community using different treatments. In all groups, Actinobacteria, Proteobacteria, Firmicutes and Bacteroidetes were the dominant phyla. After contaminated with crude oil, the relative abundance of phylum Actinobacteria was dramatically increased and occupied 81.8%. Meanwhile although strains of Bacillus were added in the bioaugmentation groups, the relative abundance of genus Bacillus was not the most abundant genus at the end of simulation tests. The crude oil contamination dramatically decreased the soil microbial diversity and bioremediation could not recover the microbial community in the short term.